Exchange-rate dynamics and the term structure of interest-rates - Kearney, C (Economic & Social Studies, 1988)
This paper examines the nature of the relationship which exists between the dynamics of exchange rate adjustments and the term structure of interest rates. In the absence of anticipated economic disturbances, there exists a well-defined negative relationship between movements in the exchange rate and the long-short interest rate differential which does not persist in the presence of anticipated disturbances. It follows that any empirical test of the relationship between the exchange rate and the term structure of interest rates necessitates the utilisation of a measure of the yield curve which is considerably more sophisticated than the differential between interest rates on assets with long and short terms to maturity. An appropriate yield curve approximation is estimated on monthly Irish data over the period 1979(4)-1986(12) and employed to examine its relationship with the rate of foreign exchange of the Irish punt over the same period.
Keywords: Exchange rates - Economics; Interest rates - Economics